Antimicrobial and Mechanical Properties of Orthodontic Acrylic Resin Containing Zinc Oxide and Titanium Dioxide Nanoparticles Supported on 4A Zeolite - Mahdiyeh Esmaeilzadeh; Baharak Divband; Bahram Ranjkesh; Fatemeh Pournaghi Azar; Fatemeh Yeganeh Sefidan; Mojgan Kachoei; Behnaz Karimzadeh (International Journal of Dentistry)
Polymethyl methacrylate (PMMA) is widely used to manufacture removable orthodontic appliances. However, since the porous structure, cold-curing acrylic resins are susceptible to bacterial adhesion and colonization. The aim of this study was to investigate the antibacterial and mechanical properties of a cold-curing PMMA resin containing ZnO and TiO2 nanoparticles supported on the 4A zeolite. ZnO and TiO2 nanoparticles supported on the 4A zeolite were synthesized. Nanoparticles were added in three compositions as ZnO/4A, TiO2/4A, and ZnO/TiO2/4A at 2wt% and 4wt% concentrations to cold-curing acrylic resin powder (SR Triplex® Cold Ivoclar Vivadent AG, FL-9494 Schaan/Liechtenstein). X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), energy dispersive X-ray (EDX), transmission electron microscopy (TEM), and dynamic light scattering (DLS) were performed to investigate the nanocomposite characteristics. A direct test method was used to assess the antibacterial properties against Streptococcus mutans, Klebsiella pneumoniae, and Escherichia coli. The surface roughness of acrylic samples was measured with a profilometer. Flexural strength was evaluated by a three-point bending test, and one-way ANOVA and Tukey’s post hoc tests were used for statistical evaluation of the data. A p value of less than 0.05 was considered statistically significant. XRD confirmed the accurate crystalline structure of synthesized nanoparticles; FE-SEM images showed nanoparticle dispersion within polymerized acryl. The addition of 2 and 4 wt% of ZnO/4A, TiO2/4A, and ZnO/TiO2/4A caused colony reduction in all types of tested microorganisms more than 99% and 100%, respectively. The mean flexural strengths of acrylic specimens containing 2wt% and 4wt% of synthesized nanoparticles were significantly lower than those of the resin without nanoparticles. Fabricated samples showed favorable antibacterial properties but decreased flexural strength.